Non‐invasive prenatal testing for trisomy 21: a cross‐sectional survey of service users' views and likely uptake. (17th January 2014) - Lewis, C; Hill, M; Silcock, C; Daley, R; Chitty, LS
<x xml:space="preserve">Abstract</x> Objective To assess the views and likely uptake of non‐invasive prenatal testing (NIPT) for trisomy 21 among potential service users in the UK. Design Cross‐sectional survey. Setting Four antenatal clinics in England and two websites. Sample A total of 1131 women and partners. Methods Questionnaire conducted with women (and partners) recruited through antenatal clinics, a random sample of members of the website Mumsnet, and viewers of the website and Facebook page of the support group Antenatal Results and Choices (ARC). Main outcome measures Factors impacting decision‐making towards prenatal testing; views on NIPT, including service delivery and likely uptake; hypothetical scenarios, focused on current screening, invasive testing, and NIPT offered to women with a high‐risk screening result. Results The vast majority (95.7%; 1071/1119; 95% CI 94.4–96.8%) thought NIPT was a positive development in prenatal care, with 88.2% (972/1103; 95% CI 86.1–90%) indicating that they would use the test, including respondents who would currently decline trisomy 21 screening (P < 0.001). Of the respondents who would have NIPT, 30.7% (299/973; 95% CI = 27.8–33.7%) said that they were 'likely' to terminate an affected pregnancy (including those who would currently decline screening or invasive testing), and 36.5% (355/973; 95% CI 33.5–39.6%) were 'not likely' to terminate an affected pregnancy. Respondents overwhelmingly indicated that safety for the baby was the most important attribute of NIPT (70.1%; 712/1015; 95% CI 67.2–73%). Conclusion Respondents were overwhelmingly positive towards the introduction of NIPT. Uptake is likely to be high, and includes women who currently decline screening as well as those who will use the test for information only. Pre‐test counselling to ensure that women understand the implications of the test result is essential.